Converting beach wrack into a resource as a challenge for the Baltic Sea (an overview). (1st February 2021) - Chubarenko, B.; Woelfel, J.; Hofmann, J.; Aldag, S.; Beldowski, J.; Burlakovs, J.; Garrels, T.; Gorbunova, J.; Guizani, S.; Kupczyk, A.; Kotwicki, L.; Domnin, D.; et al.
Abstract: The paper distinguishes beach wrack, the marine generated organic part of beach cast, as a separate management object and discusses research questions related to its management and economically viable use. Based on experiences from the Baltic Sea and existing practices from countries with different management systems clear distinction between the management of natural and anthropogenic components of cast material is seen as an essential prerequisite for developing sustainable product chains that allow beach wrack to be used as a resource of commercial value. Presenting and discussing examples from Denmark (Køge Municipality), Germany (Kühlungsborn, Rügen and Poel Island), Poland (Gulf of Gdansk), Russia (Curonian and Vistula spits) and Sweden (Kalmar municipality and Öland), social, ecological, and economic consequences of beach wrack removal are analysed to improve the attractiveness of beaches for recreational purposes. It also includes potential contribution to Baltic Sea water restoration processes through the removal of the organic part of beach cast, where indeed more studies about the chemical (nutrients, metals) composition of beach wrack are required for reliable calculation of a depuration rate. For local economies within the Baltic Sea region, the organic part of beach cast (beach wrack and terrestrial debris) has reasonable economic prospects as a renewable natural resource, e.g. for soil improvement products, in fertilisers and bio-coal production, for landfill covers (contributing to climate change mitigation), biogas generation, and even for coastal protection by providing humus-like material for accelerated dune vegetation succession. For all these recycling options the development of cost-efficient technologies for collecting beach cast on sandy as well as stony beaches and also for separating the organic part from sand and anthropogenic litter (mainly plastic), is urgently required. Amendments of legal regulations, that better reflect the dualism of beach cast are also required. In essence, dualism results from the fact that beach wrack is a part of nature (or a natural resource) when it remains on a beach. However, beach wrack immediately becomes legally categorised as waste once humans collect it irrespective of its litter content. Another legal aspect being dealt with originates from the migration of the beach wrack between water and beach, whilst it is an object of ерleagl cleaning operations only at the beach it onto the beach, but not whilst in the water. Graphical abstract: Image 1 Highlights: Approaches for sustainable use of beach wrack (BW) are described. Obstacles are discussed based on the experience from the Baltic Sea region. Research problems related to BW management in the Baltic Sea region are formulated. BW is an available, renewable, natural resource for local agro- and energy sectors. Dualism of BW management: a natural resource, that's treated as waste once collected.